1992
DOI: 10.1088/0268-1242/7/3b/007
|View full text |Cite
|
Sign up to set email alerts
|

Changeover from acoustic to optic mode phonon emission by a hot two-dimensional electron gas in the gallium arsenide/aluminium gallium arsenide heterojunction

Abstract: We have used heat pulse techniques to study the energy relaxation of a hot two-dimensional electron gas (ZOEG) in a GaAsIAIGaAs heterojunction. The 20EG was heated by applying short ( 2 loons) electrical pulses to the drainsource contacts of the device. The electrons lost energy by emitting phonons which were detected by a CdS bolometer on t h e opposite side of the GaAs substrate. A change in the nature of the phonon signal occurring at a n excitation level of about 5 p W per electron indicated a change in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 9 publications
4
23
0
Order By: Relevance
“…22 As a result, the bulklike decay modes do not contribute significantly to the hotphonon buildup in the system. However, an outgoing acoustic phonon energy flux can be measured experimentally; 31 these measurements provide useful information about the transport phenomena occurring in the QW. 32 We consider a lattice temperature, T, of 30 K. It is high enough so that it is reasonable to neglect electron gas degeneracy 23 even at low electric fields for the electron concentrations of interest in this work.…”
Section: Modelmentioning
confidence: 99%
“…22 As a result, the bulklike decay modes do not contribute significantly to the hotphonon buildup in the system. However, an outgoing acoustic phonon energy flux can be measured experimentally; 31 these measurements provide useful information about the transport phenomena occurring in the QW. 32 We consider a lattice temperature, T, of 30 K. It is high enough so that it is reasonable to neglect electron gas degeneracy 23 even at low electric fields for the electron concentrations of interest in this work.…”
Section: Modelmentioning
confidence: 99%
“…Determination of the temperature of electrons, under electric-field heating conditions in the steady state, provides useful information about the electron-phonon interactions involved in the energy relaxation process. Since at temperatures below about 30-40 K, the population of optical phonons in GaAs is negligibly small, acoustic-phonon scattering provides the only inelastic scattering mechanism [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental work concerning the acoustic-phonon-assisted energy relaxation of 2D electrons in high electron mobility transistor (HEMT) structures has been published by a large number of groups [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. It has been often reported that the energy-loss rates show a power-law dependence on the electron temperature T e with an exponent, which varies depending on the base lattice temperature (T L0 ) of measurements and also on the range of electron temperatures, but information in detail is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…However, these measurements were limited by the technique to the electron temperature range T e < 4 K. Stanton et al [3] studied the energy relaxation rate in bulk (3D) GaN samples using zero-field transport measurements to determine T e . In the low mobility samples used, this technique was applicable to a wide range of electron temperature, 1.5 K < T e < 300 K. However, in higher mobility samples, where phonon scattering makes a significant contribution to the mobility in the temperature range of interest, the technique must be used with caution [4].The main aim of the work described in this paper was to use the zero-field transport techniques to extend the measurements of Lee et al to higher electron tempera- …”
mentioning
confidence: 99%